Optimalisasi Aplikasi SIDeKa-Pro Dalam Upaya Peningkatan Kedisiplinan Pengisian Data 10 Besar Penyakit Rawat Jalan Melalui Pembuatan Standar Operasional Prosedur (SOP) - Hikmawan Suryanto (Jurnal Repositor, 2023)
Recording and reporting has now undergone a process of evolution from paper to digital. Likewise, the recording and reporting of health services in the City of Probolinggo uses the SIDeKa-Pro application. In practice, there are still health service facilities that are late in filling out data in the SIDeKa-Pro application. As many as 56% of health care facilities in Probolinggo City in 2020 were late in filling out the top 10 outpatient disease data in the SIDeKa-Pro application. Then, as many as 38% of health service facilities in Probolinggo City in January - March 2021 were late in filling out data on the top 10 outpatient diseases in the SIDeKa-Pro application. The purpose of this study was to determine the level of data occupancy of the top 10 outpatient diseases before and after standard operating procedures (SOP). This study uses a cohort study. This type of research is experimental, namely one shoot case study. The population in this study were all data managers in health facilities who had registered in the SIDeKa-Pro application as many as 32 health care facilities. The sampling technique used is total sampling. The results showed that the SOP for data entry in SIDeKa-Pro was able to increase the discipline of health care facility managers in filling out data for the top 10 outpatient diseases in the SIDeKa-Pro application. Suggestions are all organizations that have applications, SOPs should be made.